A COMPREHENSIVE SYSTEMATIC REVIEW OF THE ASSOCIATION BETWEEN VISCERAL OBESITY AND INCREASED CARDIOMETABOLIC DISEASE RISK: A SYSTEMATIC REVIEW OF RANDOMIZED CONTROLLED TRIALS AND PRIMARY STUDIES - Jeffy Marta (The Indonesian Journal of General Medicine, 2026)
Introduction: Visceral adipose tissue (VAT) is a metabolically active, pro-inflammatory fat depot distinct from subcutaneous fat. Body mass index (BMI) and waist circumference (WC) cannot discriminate VAT from subcutaneous fat, misclassifying patients with normal-weight central adiposity. This review synthesised primary evidence linking visceral obesity to cardiometabolic disease across sixteen outcome domains. Methods: The study strictly adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. Eligible designs comprised randomized controlled trials, cohort, case-control and observational studies quantifying VAT by imaging (CT, MRI, DXA) or validated surrogates (METS-VF, VAI, CVAI). Systematic reviews were excluded from primary tabulation. Two reviewers independently screened, extracted data and appraised risk of bias using Newcastle-Ottawa Scale and RoB 2; certainty was graded with GRADE. Synthesis was narrative and tabular. Results: Fifty-two primary studies (36 observational, 16 RCTs) encompassing >400,000 participants were included. Incident CVD adjusted HRs ranged from 1.62 to 2.78. VAT predicted coronary heart disease independently of WC (HR 1.15 per SD), recurrent MACE (aHR 2.71), cardiovascular mortality (aHR 1.23 per SD; C-statistic 0.73), and all-cause mortality (HR 4.90 highest quartile). T2DM associations were markedly sex-divergent: adjusted ORs 2.62 in men and 32.49 in women. VAT predicted hypertension (OR 5.07) and metabolic syndrome (OR per SD 4.7 women, 4.2 men), persisting after BMI, WC and SAT adjustment. In normal-weight individuals, highest VAT quartile conferred 9-fold increased metabolic syndrome risk (OR 9.3). Randomized evidence demonstrated VAT modifiability: liraglutide 3.0 mg reduced VAT by 12.49% versus 1.63% with placebo (p<0.0001); combined exercise plus GLP-1 RA reduced metabolic syndrome severity z-score by -0.48 and hsCRP by 43%. Risk of bias was low to moderate. GRADE certainty was moderate for T2DM, hypertension, metabolic syndrome and VAT modifiability; low for cerebrovascular events. Discussion: VAT consistently outperforms SAT in predicting outcomes; associations persist after anthropometric adjustment; dose-response and cumulative-exposure gradients are demonstrated; effects are stronger in women; risk exists in normal-weight individuals; VAT is reversible under randomized intervention. Visceral and hepatic fat are related but distinct. Incremental predictive value beyond established risk scores is modest; VAT assessment is best as reclassification tool for intermediate-risk individuals. Conclusion: Visceral obesity is an independent, dose-dependent, sex-modified and therapeutically modifiable determinant of cardiometabolic disease, exerting effects not captured by BMI or WC alone. Clinical practice should move towards phenotype-centric assessment using imaging where available and validated surrogates where not, prioritising interventions with demonstrated VAT efficacy. Future research should establish population-specific VAT thresholds and test whether VAT-guided treatment improves hard outcomes.